Economic Analysis of Potato Production under Bung Practice in Solukhumbu District, Nepal - Karki, Sagar; Ghimire, Suman; Bhattarai, Sony; Chhetri, Sanjita Khati; Poudel, Puspa (Agronomy Journal of Nepal, 2025)
In 2023, an economic evaluation of potato cultivation within the bung system was carried out in Nepal’s Solukhumbu district. A purposive sampling was performed to choose sixty potato-farming households from the Solududhkunda, Thulung Dudhkosi, and Sotang rural municipalities. A pre-tested semi-structured interview schedule, direct observation, focus group discussions, and key informant interviews were used as primary data collection. Whereas, secondary data were obtained from journals, research papers, bulletins, and reports published by diverse organizations. Data were evaluated via descriptive statistics. The data showed that the majority of bung potato farmers were women. “Producers-Collector-Wholesalers-Consumer” was the primary marketing channel for bung potato in the study area. The average cost of potato production was NRs. 89,269.57 per hectare, with land preparation and plantation accounting for the largest share. The gross income and net return were NRs. 216,181.40 and NRs. 126,911.80 per hectare, respectively, yielding a benefit-cost ratio of 2.4, which confirms the high profitability of bung potato cultivation. Around 80% of the producer’s share in the consumer price was estimated with a price spread of 20%. The major issues in bung potato farming were identified as lack of technical expertise, lack of improved variety, shortage of labor, weather uncertainty, and disease and insect pests.